An unconventional weekly economic activity index for Germany - Sercan Eraslan; Thomas Götz (Deutsche Bundesbank, 2020)
We develop an unconventional activity index for the German economy at weekly frequency in order to monitor economic developments at the current end in real time. The index contains nine high-frequency, rather unconventional weekly indicators. These are augmented by monthly industrial production and quarterly gross domestic product. The weekly activity index is then calculated as the common factor of the mixed-frequency dataset. It turns out that the index exhibits a high correlation with quarterly GDP growth and is thus able to serve as a reliable weekly coincident indicator for economic activity in Germany.
Keywords: 330; business cycle; economic indicator; factor analysis